Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.2320/matertrans.45.947
|View full text |Cite
|
Sign up to set email alerts
|

Adherence of Porcelain Veneered on Titanium with an Intermediate Plasma-Sprayed Zirconia Layer

Abstract: Porcelain veneered on pure titanium with an intermediate plasma-sprayed ZrO 2 bond coat layer was investigated in this study. The pure porcelain coating veneered on Ti was used as a control. The specimens were subjected to four-point bending test to measure the bonding strength. The fractograph, microstructure, surface roughness, and phase of plasma-sprayed ZrO 2 bond coat were examined. The phase constituents at the location of adhesive failure of the fractured specimens were investigated by thin-film X-ray d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…The use of Si 3 N 4 , chrome, SiO 2 , and TiO 2 as intermediate layers to minimize Ti oxidation for Ti-porcelain restorations has been investigated ( Ref 4,[8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The use of Si 3 N 4 , chrome, SiO 2 , and TiO 2 as intermediate layers to minimize Ti oxidation for Ti-porcelain restorations has been investigated ( Ref 4,[8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…According to our previous studies, 12,13) the location of adhesive failure occurred near the Ti oxide/Ti interface and even slightly inside the uppermost Ti substrate. This revealed that the porcelain/Ti oxide interface possesses fairly high bonding strength, i.e.…”
Section: Introductionmentioning
confidence: 64%
“…The mean T deb collected for all the tested groups are reported in Table IV. Significant differences were found among groups as determined by the 1-way ANOVA (F [3,36]¼8.6, P<.05). The mean (AESD) debond strengths for both the control (23.51 AE2.94 MPa) and type 1 coating (25.97 AE2.53 MPa) were near the acceptable lower limit of 25 MPa.…”
Section: Resultsmentioning
confidence: 88%
“…The bond strength values obtained for the group that received the ceramic slurry were in the range of 26 to 28 MPa. Lo et al 36 reported that the application of an intermediate plasma-sprayed ZrO 2 layer provides a higher surface roughness, which enhances the mechanical bond at the ZrO 2 -porcelain interface and acts as a sufficient oxygen diffusion barrier at 800 C to prevent the oxidation of Ti at the Ti-ZrO 2 interface. Similarly, Chou and Chang 35 reported that the bonding strength…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation